Phenotypic Identification of Lactobacillus from Breast Milk Based on Their Ability to Ferment Sugars - Arihantana, Ni Made Indri Hapsari; Puspawati, Ni Nyoman (Journal of Veterinary and Animal Sciences, 2017)
The purpose of this study was to identify the species of Lactobacillus which has the potency as superior probiotic based on their ability to ferment sugars. The study was conducted in two steps, the first was a confirmation test of the five lactic acid bacteria (LAB) isolates of breast milk A1, A6, A8, B8, and B10b. All of the LAB isolates were Gram positive rod and negative catalase. This shows that all of the isolates were of the genus of lactic acid bacteria and readily for the second step testing. The second step was to determine the LAB isolates ability to ferment 50 sugars (carbohydrates) using API 50 CHL kit. Results from the API 50 CHL kit test showed that the 5 LAB isolates were of indigenous LAB with the identification level of 88,7% - 99,9%. The species found were three spesies of Lactobacillus plantarum-1 (Lactobacillus plantarum-1 A1, Lactobacillus plantarum-1 A8, Lactobacillus plantarum-1 B8),and 2 spesies of Lactobacillus rhamnosus (Lactobacillus rhamnosus A6, and Lactobacillus rhamnosus B10b), respectively.